Арктична політика КНР: виклики регіональній безпеці (1990-ті – 2020-ті рр.) - Горобець, О. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2021)
У статті проаналізовано еволюцію арктичної політики Китаю, яка за
три десятиліття розширилась від окремих полярних наукових досліджень
до статусу країни-спостерігача в Арктичній раді та наявності державної
арктичної стратегії. КНР та РФ налагодили взаємовигідне співробітництво в Арктичному регіоні в таких умовах, коли за багатьма напрямками
присутні принципові протиріччя між країнами.
Захід не мав довготермінової стратегії, здатної зреагувати на сучасні
виклики безпеки, зокрема в Арктичному регіоні. Коли у 2007–2008 роках
Росія вдалася до спроб повернути собі втрачені позиції на світовій арені,
Китай ставав все впливовішим гравцем у світі. Якщо до цього Арктика десятки років була за межами ліній суперництва, питання Крайньої Півночі, як арени військової конкуренції, почало посідати перші місця.
Окремий аспект – швидка мілітаризація Арктичного регіону після 2014
року, насамперед, через зміни в російській військовій стратегії, яка поширюється на Північ. Це призвело до напружених відносин між Сполученими Штатами та Росією. Китай поки не вдавався до розширення своєї військової потуги на Арктику. Тому військовим методам протиставляється китайська політика впливу в інфраструктурній та економічній сферах, а
також оцінюється їх ефективність. У статті здійснено аналіз перспектив Північного морського шляху
стати міжнародною морською транспортною артерією в умовах, коли РФ з 2014 року переправила значні військові ресурси в Арктику, зокрема для закріплення за собою прав на контроль Північного морського шляху. The article analyzes the evolution of China's Arctic policy, which has expanded
over three decades from individual polar research to observer status in
the Arctic Council and the existence of a state Arctic strategy. China and Russia
have established mutually beneficial cooperation in the Arctic region in such conditions,
when in many areas there are fundamental contradictions between the
countries.
The West did not have a long-term strategy capable of responding to current
security challenges, including in the Arctic. When Russia tried to regain lost positions
on the world stage in 2007-2008, China became an increasingly influential
player in the world. If before the Arctic had been outside the lines of rivalry for
decades, the question of the Far North as an arena of military competition began
to take first place.
China has become a long-term threat to both the United States and Russia.
In previous years, with the help of the China, Moscow had the opportunity to receive
the necessary investments and technologies for large-scale Arctic projects.
The more Beijing attempts to establish itself as an influential player in the Arctic,
the more the threat to other Arctic countries will grow.
The Russian Federation has positioned itself as a leader in the region. The
country's policy was aimed at strengthening this status through regional control
and expansion of the military presence. This led to a response from the United
States and NATO countries. In Russia it was assessed as a threat.
The question arises as to what the strategy of the United States should be,
and whether it will be possible to resist the costly arms race. If not, then the competition
will be concentrated in the political and economic spheres.
A particular aspect is the rapid militarization of the Arctic region after 2014,
primarily due to changes in Russia's military strategy, which extends to the North.
This has led to the tensions between the United States and Russia. China has not
yet resorted to expand its military power in the Arctic. China's policy of economic
and infrastructural influence is opposed to military methods. The effectiveness
of Chinese non-military methods of influence is assessed.
The article analyzes the prospects of the Northern Sea Route to become an
international maritime transport artery at the time when the Russian Federation
since 2014 has transferred significant military resources to the Arctic, including
to secure the right to control the Northern Sea Route.